FROM TIKTOK TO CHECKOUT: How Social Media Marketing Influences Gen Z’s Purchase Intention for Halal Cosmetics through Brand Trust and Perceived Value - Aribtha, Dwi Noviola; Salim, Muhartini (UTSAHA: Journal of Entrepreneurship, 2025)
For Generation Z, social media has become an inseparable aspect of daily life, influencing various aspects of consumer behavior, including purchasing decisions. Among the numerous social media platforms, TikTok has emerged as a powerful tool in shaping consumer perceptions, particularly in the beauty and cosmetics industry. In the context of halal cosmetics, TikTok plays a crucial role in enhancing perceived value and strengthening brand trust, both of which are essential factors in influencing purchase intention. This study aims to examine the impact of social media marketing via TikTok on purchase intention, with brand trust and perceived value acting as mediating variables. The research focuses on halal cosmetic products in Bengkulu Province, employing a quantitative methodology. Data collection was conducted through a structured questionnaire, with respondents providing their answers on a five-point Likert scale. A minimum sample size of 95 respondents was determined for this study. The data analysis was carried out using Smart PLS 4.0 to evaluate the relationships between the variables. The findings reveal that social media marketing has a significant and positive effect on purchase intention. Furthermore, brand trust and perceived value serve as mediators, reinforcing the relationship between social media marketing and purchase intention. These results highlight the importance of social media strategies in increasing consumer trust and perceived product value, ultimately driving purchase decisions for halal cosmetics.